Methodology of teaching a foreign language as a factor in the formation of professional competence of students – future economists - A. A. Pshikhacheva (Вестник Майкопского государственного технологического университета, 2023)
The article is devoted to studying theoretical and methodological foundations of teaching a foreign language as a factor in the formation of professional competence of students – future economists. The author substantiates the relevance and significance of the research topic in the context of the prospects for social demand for specialists in the economic sphere. Skills the formation and development of which is necessary to meet this request have been considered, the model of “skills of the future” specified.It has been noted that in order to initiate and fund this model, which expresses the full-fledged («closed») professional competence of students - future economists, there is a need to form an additional, “third skill”, namely mastering a foreign language (foreign language skill). The problem, therefore, lies in the need to select an adaptive and effective methodological approach (model of teaching methodology), regardless of the teaching format adopted in the educational organization.The purpose of the research is to select the best alternative and its argumentation. To achieve this goal, the following research methods have been used: general scientific (dialectical, analysis and synthesis of available literature data, comparisons and analogies, annotation, note-taking and abstracting of information obtained from modern scientific sources) methods, special (systemic, comparative analysis, etc.) methods. The results of the research show that the most optimal methodology for teaching a foreign language as a factor in the formation of professional competence of students – future economists is the methodology of task-based learning (TBL).